2016
DOI: 10.1016/j.cmi.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke and transient ischaemic attack after herpes zoster

Abstract: We assessed the association of herpes zoster (HZ) with stroke/transient ischaemic attack (TIA) in the general population according to age with controlling risk factors for stroke, using a nationwide representative cohort. The study was based on a prospective dynamic cohort consisting of 1 million Koreans representing all age groups, genders and geographical areas in the Korea Health Insurance Database. New events of stroke/TIA and HZ were identified using the diagnostic codes in the International Classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…demonstrated to have a 1.5-2.0 times increased incidence of HZ over that in nonimmunosuppressed patient populations of similar age (2). Second and consistent with several other studies (6)(7)(8)14,17), we demonstrated that more serious and complex forms of HZ are attended by the highest rates of stroke. We performed this analysis by separating HZ by ICD code into zoster without complications as well as zoster with complications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…demonstrated to have a 1.5-2.0 times increased incidence of HZ over that in nonimmunosuppressed patient populations of similar age (2). Second and consistent with several other studies (6)(7)(8)14,17), we demonstrated that more serious and complex forms of HZ are attended by the highest rates of stroke. We performed this analysis by separating HZ by ICD code into zoster without complications as well as zoster with complications.…”
Section: Discussionsupporting
confidence: 90%
“…In a subset of subjects younger than 40 years, stroke was increased over the study period, with an adjusted hazard ratio of 2.42. Three other recent studies of alternative design including 1 single health system analysis and 2 registry‐based cohort studies produced similar findings.…”
Section: Discussionsupporting
confidence: 61%
“…Only one other study specifically assessed the association between TIA and HZ 7 ; the other studies included TIA as part of a composite vascular event together with stroke. 9,20 In their study with a median follow-up of 6.3 years, Breuer et al 7 reported a 15% increase in the risk of suffering a TIA in their population of 106,601 patients with HZ (adjusted hazard ratio, 1.15; 95% CI, 1.09-1.21). Our findings agree with these, also with regard to the increased risk reported in younger patients with HZ (adjusted hazard ratio in the HZ group aged 18-40 years, 2.42; 95% CI, 1.34-4.36).…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] Herpes zostereassociated vasculopathy may be cranial or extracranial and may result in transient ischemic attack (TIA) and stroke. 5 Over the past few years, an association between HZ and an increased risk of stroke, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] TIA, 7,9,16,20 myocardial infarction (MI), 7,11,16 and acute coronary syndrome 21 has been supported by several studies [7][8][9][10][11][17][18][19][20][21] and meta-analyses, [12][13][14][15][16]22 most of which were conducted outside the United States. In the United States, data are limited to only 3 studies that reported an increased likelihood of MI 10 and stroke 11,17 after HZ.…”
mentioning
confidence: 97%
“…We included self-controlled case series since these studies have a design akin to that of an efficient cohort study that minimizes confounding and produces measures of association, unlike a traditional case series [ 34 ]. The studies sampled populations from six countries including enrollees of the national health insurance systems in Taiwan [ 23 , 25 , 28 , 29 ] and South Korea [ 24 ], Danish hospital and prescription drug users [ 26 ], British primary care patients [ 22 , 31 ], American Medicare enrollees 65 years and older [ 32 ], residents 50 years and older in Olmsted County (MN, US) [ 30 ], enrollees of four private insurers in Germany [ 33 ] and residents of Västra Götaland County, Sweden [ 27 ]. All included studies performed retrospective reviews of electronic medical record databases; no study prospectively followed patients.…”
Section: Resultsmentioning
confidence: 99%